PREVENTIVE EFFORTS IN LAW ENFORCEMENT OF CYBER FRAUD BASED ON ARTIFICIAL INTELLIGENCE - Jalaluddin Jalaluddin; Muharrrir Muharrir; Agung Munandar; Muhammad Nahyan Zulfikar (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
Artificial Intelligence has become a new aspect of social life in 2020, as the widespread use of technology has led to the development of devices with Artificial Intelligence as a key feature. Furthermore, Artificial Intelligence with more sophisticated features continues to develop and can be accessed by installing a dedicated program or through relevant websites. Cybercrimes are inherently diverse and not limited to online fraud. However, the growing phenomenon of online fraud stems from the close connection between perpetrators and victims, a strong relationship driven by numerous factors, such as urgency and high needs. This study aims to determine preventive measures for law enforcement against AI-based online fraud. The research method employed is a normative juridical approach with a conceptual approach. The findings demonstrate that preventive measures for law enforcement against Artificial Intelligence based online fraud can be implemented from three perspectives: from the perspective of the public as users, from the perspective of law enforcement as the spearhead of law enforcement, and from the perspective of the regulation itself as the legal umbrella.